Deficiency of glucocorticoid receptor in bone marrow adipocytes has mild effects on bone and hematopoiesis but does not influence expansion of marrow adiposity with caloric restriction - Schill, Rebecca L.; Visser, Jack; Ashby, Mariah L.; Li, Ziru; Lewis, Kenneth T.; Morales-Hernandez, Antonio; Hoose, Keegan S.; Maung, Jessica N.; Uranga, Romina M.; Hariri, Hadla; Hermsmeyer, Isabel D. K.; Mori, Hiroyuki; et al. (Frontiers in Endocrinology, 2024)
Introduction Unlike white adipose tissue depots, bone marrow adipose tissue (BMAT) expands during caloric restriction (CR). Although mechanisms for BMAT expansion remain unclear, prior research suggested an intermediary role for increased circulating glucocorticoids. Methods In this study, we utilized a recently described mouse model (BMAd-Cre) to exclusively target bone marrow adipocytes (BMAds) for elimination of the glucocorticoid receptor (GR) (i.e. Nr3c1) whilst maintaining GR expression in other adipose depots. Results Mice lacking GR in BMAds (BMAd-Nr3c1-/-) and control mice (BMAd-Nr3c1+/+) were fed ad libitum or placed on a 30% CR diet for six weeks. On a normal chow diet, tibiae of female BMAd-Nr3c1-/- mice had slightly elevated proximal trabecular metaphyseal bone volume fraction and thickness. Both control and BMAd-Nr3c1-/- mice had increased circulating glucocorticoids and elevated numbers of BMAds in the proximal tibia following CR. However, no significant differences in trabecular and cortical bone were observed, and quantification with osmium tetroxide and μCT revealed no difference in BMAT accumulation between control or BMAd-Nr3c1-/- mice. Differences in BMAd size were not observed between BMAd-Nr3c1-/- and control mice. Interestingly, BMAd-Nr3c1-/- mice had decreased circulating white blood cell counts 4 h into the light cycle. Discussion In conclusion, our data suggest that eliminating GR from BMAd has minor effects on bone and hematopoiesis, and does not impair BMAT accumulation during CR.